Unscrambling jumbled sentences: An authentic task for English language assessment? - Lanteigne, Betty (Studies in Second Language Learning and Teaching, 2017)
Jumbled sentence items in language assessment have been criticized by some authors as inauthentic. However, unscrambling jumbled sentences is a common occurrence in real-world communication in English as a lingua franca. Naturalistic inquiry identified 54 instances of jumbled sentence use in daily life in Dubai/Sharjah, where English is widely used as a lingua franca. Thus it is seen that jumbled sentence test items can reflect real-world language use. To evaluate scrambled sentence test items, eight test item types developed from one jumbled sentence instance (“Want taxi Dubai you?”) were analyzed in terms of interactivity and authenticity. Items ranged from being completely decontextualized, non-interactive, and inauthentic to being fully contextualized, interactive, and authentic. To determine appropriate assessment standards for English tests in schools in this region, the English language standards for schools and English language requirements for university admission in the UAE were analyzed. Schools in Dubai/Sharjah use Inner Circle English varieties of English (e.g., British or American English) as the standard for evaluation, as well as non-native-English-speaker varieties (e.g., Indian English(es)). Also, students applying to English-medium universities in the UAE must meet the required scores on standardized English tests including the IELTS and TOEFL. Standards for evaluation of communication in English involving tasks of jumbled sentences in classroom tests must reflect the language learning goals of the school and community. Thus standards for classroom assessment of English in Dubai/Sharjah are determined by local schools’ and universities’ policies.